The Limits of Auteurism : Case Studies in the Critically Constructed New Hollywood - Godfrey, Nicholas, 1986- (Book collections on Project MUSE., 2018)
The New Hollywood era of the late 1960s and early 1970s has become one of the most romanticized periods in motion picture history. The Limits of Auteurism challenges many of these assumptions. The book explores how distribution and critical reception determined the parameters of the New Hollywood canon.